IOT Cloud Based Real Time Automobile Monitoring System - M Renu Babu; B P. Pramod Reddy; B. Manisha; M. Anusha; S. Vaishnavi (International Journal of Engineering and Management Research, 2021)
Smart sensing has had a significant impact on defining our future in recent years. The field of IOT is a recent technical innovation that has caused a change in lifestyle (Internet of things). IoT refers to the internetworking of physical equipment and other items that are equipped with electronics, software, sensors, and network connectivity to allow data to be collected from them. Transportation is a booming industry in India, with the number of vehicles on the road increasing by the day. Monitoring vehicle metrics such as gasoline, temperature, and battery level without having to touch the car is perfect. In this digital age, a digital locking mechanism is desperately needed. When your vehicle is not with you, vehicle tracking is also essential. Here, car tracking is designed using GPS to conveniently locate the user's vehicle. The IoT cloud-based real-time automotive monitoring system is capable of monitoring our vehicle's metrics such as fuel level, battery level, engine temperature, and speed, as well as tracking the driver's alcohol percentage via an Android application. We receive an alert when one of these metrics crosses a certain threshold. Its Smart RFID digital key secures your vehicle even more than keys do. We may save our vehicle documents, driver's licences, insurance copies, and other documents in this project's Android application. Whenever an accident occurs, send a message to trusted people with the location.